An international competition policy : Do we need it? Is it feasible? (1999)
States arguments in favour of the internationalisation of competition policy as well as the counter-arguments. Indicates that the case in the former is strong but the case for a multilateral approach is also convincing, states however that there are dangers in following too closely the exiisting WTO model.
Keywords: COMPETITION POLICY